Business English in the Globalized Economy: Trends and Insights from a Literature Review - Yetti, Dzulhijjah; Nava, Lilian Nethania; Rahmat, Hayatul Khairul (PT Hakhara Akademia Indonesia, 2024)
The globalization of economic activities has intensified cross-border communication, positioning Business English as a critical tool in international trade, multinational corporations, and global professional environments. English has evolved beyond a general lingua franca into a specialized medium shaped by business practices, digital communication, and intercultural interaction. This literature review examines key trends and insights related to Business English in the globalized economy by synthesizing peer-reviewed international studies published over the past two decades. The review explores the conceptualization of Business English, its role in global business communication, emerging trends influenced by digitalization and remote work, and the implications for workforce competence and education. Findings indicate that Business English increasingly emphasizes pragmatic competence, intercultural communication skills, and adaptability to digital business contexts rather than native-like linguistic accuracy. The literature also highlights persistent inequalities in access to Business English proficiency, particularly between developed and developing economies, and across organizational hierarchies. The review concludes that Business English functions as a strategic economic resource that shapes employability, organizational performance, and global competitiveness. Strengthening Business English education requires aligning language training with real-world business practices, technological change, and intercultural awareness. Future research should focus on longitudinal workplace studies, digital business discourse, and inclusive language policies in global organizations.